Effect of yeast concentration and fermentation time on the characteristics of tuak from coconut sap - Thobie E. B Kaban; Ni Putu Suwariani; Ida Bagus Wayan Gunam (Hasanuddin University Food Science and Technology Study Program, 2022)
Tuak is a traditional fermented drink made from the sap of the Palmae family that is favored by rural communities. The quality of tuak varies greatly and depends on the type of microbe that contaminates the sap raw material. This research aimed to get the best yeast concentration and fermentation time, to get the best characteristics of tuak from coconut sap. The first factor was yeast concentration (0, 2, 4, 6, and 8%). The second factor was fermentation time (24, 48, 72, 96, and 120 hours). The research was grouped based on the processing time and got 50 units of the samples. The experiment was carried out at room temperature (± 30°C). The parameter of this research was sensory evaluation test, alcohol content, pH, total dissolved solids, and total sugar. The data of this research were analyzed with analysis of variance, followed by the Duncan’s test. The results showed that yeast concentration 4% w/v and fermentation time of 72 hours produced the best characteristics of tuak from coconut sap with the characteristics of sensory test for the alcohol flavor was between like to really like (4.30), the sour flavour was neutral to like (3.59), the sweet flavour was like to really like (4.85), and overall acceptance was like to really like (4.95) with alcohol content (9.38%), pH (4.2), total dissolved solids (7.52 mg/L) and total sugar (1.54%). The addition of starter culture can speed up the fermentation process and at the same time improve the quality of tuak from coconut sap.